Comparison of the Acute Effects of Kinesio Taping and Sleeper Stretching on the Shoulder Rotation Range of Motion, Manual Muscle Strength, and Sub-Acromial Space in Pitchers with Glenohumeral Internal Rotation Deficit - Chi-Ling Lo; Ya-Hsin Hsueh; Chun-Hou Wang; Hsiao-Yun Chang (Medicina, 2021)
Background and Objectives: Sleeper stretching (SS) can improve the shoulder’s range of motion (ROM) for pitchers with glenohumeral internal rotation deficit (GIRD). However, no evidence has proven the effect of Kinesio taping (KT) on shoulder strength and ROM. Therefore, this study compared the effects of SS and KT on shoulder rotation ROM, muscle strength, and sub-acromial distance in pitchers with GIRD. Materials and Methods: Thirty-one pitchers with GIRD were allocated into control, KT, and SS groups. Shoulder rotation ROM, muscle strength, and sub-acromial space were measured before and after treatment with SS or KT. Results: The results revealed that KT and SS significantly enhanced shoulder rotation ROM in pitchers with GIRD. External rotator strength significantly increased following KT but significantly decreased after SS. KT and SS exerted no effects on the sub-acromial space. Conclusions: KT and SS improve shoulder rotation ROM in pitchers with GIRD. In addition, KT improves shoulder external rotator strength, and SS reduces it.